Leishmania major Infection in Synanthropic Rodents: Evidence for the Urbanization of Zoonotic Cutaneous Leishmaniasis (ZCL) in Southern Iran - Saeed Shahabi; Kourosh Azizi; Qasem Asgari; Bahador Sarkari (Canadian Journal of Infectious Diseases and Medical Microbiology)
Cutaneous leishmaniasis is of particular importance in southern Iran. This study aimed to investigate the infection of rodents with Leishmania major in an urban area of Fars Province, located in southern Iran. Rodents were trapped and samples from the liver, spleen, and skin were collected. Impression smears were prepared from these tissues and any skin lesions and were examined microscopically. In addition, a portion of the samples were preserved for subsequent DNA extraction. A total of 41 rodents belonging to three species were caught from 10 trapping stations in gardens or houses within the area. The caught rodent species were Rattus rattus (n = 25, 60.97%), Mus musculus (n = 15, 36.58%), and Meriones persicus (n = 1, 2.5%). Leishmania amastigotes were seen in the spleen tissue smear of 6 (2.43%) of the rodents, including 4 of R. rattus and 2 of M. musculus. Skin lesions were observed on the muzzles of two R. rattus and one M. musculus. Samples taken from these lesions tested positive for Leishmania infection. Leishmania DNA was detected in 18 (43.9%) rodents, including 11 R. rattus, 6 M. musculus, and one M. persicus, based on DNA sequencing of the ITS2 gene and PCR of the kDNA. Phylogenetic reconstruction revealed that the parasite infecting the rodents was L. major. The detection of Leishmania infection in these rodents in urban areas raises concerns about the urbanization of cutaneous leishmaniasis caused by L. major. This urbanization poses unique challenges for control and prevention efforts.